Enoyl ACP Reductase as Effective Target for the Synthesized Novel Antitubercular Drugs: A-State-of-the-Art - D. Joshi, Shrinivas; R. Dixit, Sheshagiri; A. More, Uttam; Aminabhavi, Tejraj; H. Kulkarni, Venkatrao; K. Gadad, Andanappa (Mini Reviews in Medicinal Chemistry, 2014)
The emergence of drug resistant strains of important human pathogens has created an urgent necessity to find new targets and novel antitubercular agents. According to the literature survey, we noticed that enoyl ACP reductase is one of the most promising targets. This enzyme is the most important catalyst for the FAS II synthesis of mycolic acid, which is the most essential component of the mycobacterial cell wall. This review summarizes the progress made in the design of enoyl ACP reductase inhibitors and the role played by 3D-structure of the enzyme in drug design process.
Keywords: Enoyl ACP reductase inhibitors